A Meta-analysis of Retinal Cytoarchitectural Abnormalities in Schizophrenia and Bipolar Disorder - Lizano, Paulo (Schizophr Bull, 2020)
BACKGROUND: Schizophrenia (SZ) and bipolar disorder (BD) are characterized by reductions in gray matter and white matter. Limitations in brain imaging have led researchers to use optical coherence tomography (OCT) to explore retinal imaging biomarkers of brain pathology. We examine the retinal layers that may be associated with SZ or BD. METHODS: Articles identified using PubMed, Web of Science, Cochrane Database. Twelve studies met inclusion for acutely/chronically ill patients. We used fixed or random effects meta-analysis for probands (SZ and BD), SZ or BD eyes vs healthy control (HC) eyes. We adjusted for sources of bias, cross-validated results, and report standardized mean differences (SMD). Statistical analysis performed using meta package in R. RESULTS: Data from 820 proband eyes (SZ = 541, BD = 279) and 904 HC eyes were suitable for meta-analysis. The peripapillary retinal nerve fiber layer (RNFL) showed significant thinning in SZ and BD eyes compared to HC eyes (n = 12, SMD = −0.74, −0.51, −1.06, respectively). RNFL thinning was greatest in the nasal, temporal, and superior regions. The combined peripapillary ganglion cell layer and inner plexiform layer (GCL-IPL) showed significant thinning in SZ and BD eyes compared to HC eyes (n = 4, SMD = −0.39, −0.44, −0.28, respectively). No statistically significant differences were identified in other retinal or choroidal regions. Clinical variables were unrelated to the RNFL or GCL-IPL thickness by meta-regression. CONCLUSION: The observed retinal layer thinning is consistent with the classic gray- and white-matter atrophy observed on neuroimaging in SZ and BD patients. OCT may be a useful biomarker tool in studying the neurobiology of psychosis.